2020
DOI: 10.1371/journal.pone.0237436
|View full text |Cite
|
Sign up to set email alerts
|

Decadal variability and recent summer warming amplification of the sea surface temperature in the Red Sea

Abstract: Under climate change, regional Sea Surface Temperature (SST) changes are a crucial factor affecting marine ecosystems, which thrive only within a certain thermal limit. Thirty-seven years of monthly gridded Optimum Interpolation SST data from 1982 to 2017 were used to investigate the decadal variability of this parameter in the Red Sea during the summer season, in relation to large-scale climate variability. We identified a non-uniform warming trend beginning around the mid-1990s over the whole basin, with a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…These results support the previous finding of Alawad et al (2020) [19] that the whole RS has experienced a nonuniform warming trend since 1996, which has amplified over the northern half to reach 0.04 • C year −1 -approximately 4 times higher than the global trend.…”
Section: Physical Mechanismssupporting
confidence: 92%
See 1 more Smart Citation
“…These results support the previous finding of Alawad et al (2020) [19] that the whole RS has experienced a nonuniform warming trend since 1996, which has amplified over the northern half to reach 0.04 • C year −1 -approximately 4 times higher than the global trend.…”
Section: Physical Mechanismssupporting
confidence: 92%
“…In addition to this, the annual mean SST shifted from 27.4 • C in 1985-1993 to 28.1 • C in 1994-2007 [18]. Recently, Alawad et al (2020) [19] found that the warming trend over the northern half of the RS is 0.04 • C year −1 , which is almost 4 times higher than the global trend, and over the southern half it is 0.01 • C year −1 , while the whole basin trend is 0.029 • C year −1 [20]. As a consequence of this intense warming trend, the growth of central Red Sea coral has decreased [21,22], as has the chlorophyll concentration over the northern half of the basin [23].…”
Section: Introductionmentioning
confidence: 88%
“…Further analysis of the lead-lag correlation revealed a 1-3 month lag, where the AMO index was found to lead the PC time series of mode 1 (Figure 11A). The warming of the Gulf 's SST in response to the AMO warming peaks was consistent with the findings of Alawad et al (2020) within the Red Sea; it is likely attributable to changes in the upper troposphere (200 hPa) meridional winds (namely the Circum-Global Teleconnection; Ding and Wang, 2005). These changes impose warm air temperatures (Lu et al, 2002;Hong et al, 2017) across the Eurasian continents.…”
Section: Sst Temporal Variability and Sst Modes In Thesupporting
confidence: 77%
“…For example, the Red Sea is influenced by the Atlantic Multidecadal Oscillation (AMO) and higher warming trends coincide with the positive phase of this oscillation, and thus the SST trend is amplified (Krokos et al, 2019). Alawad et al (2020) supported this notion and revealed that current warming for the Red Sea is largely amplified by the overlap of warming signals between the AMO and the Silk Road Pattern (SRP) in the non-uniform warming trends over the Red Sea basin, and thus might in fact decrease over the next few decades. Although it should be noted that Mann et al (2020) did not support the presence of an internally generated multidecadal oscillatory signal in the last millennium.…”
Section: Thermal Projections Under Future Scenariosmentioning
confidence: 99%